ANALISIS FINANSIAL INVESTASI USAHATANI PEMBIBITAN SAPI PERANAKAN SIMMENTAL DI KABUPATEN SLEMAN - SHANTI ERMAWATI (Universitas Sebelas Maret, 2008)
The research was conducted to determine the feasibility of financial investment on beef cattel breeding farming. Research was done from January to May 2007, located in Sleman District.